Sexual Harassment in News Gender Violence in Tempo.co Media and Newsroom Narratives (Sara Mills Critical Discourse Analysis) - Hartutik; Suminto A Sayuti (Britain International for Academic Research (BIAR) Publisher, 2023)
This study aims to describe the position of subjects-objects and writer-reader positions on news topics of gender violence against women in the media Tempo.co December 2021. This research takes a qualitative approach with the critical discourse analysis method of Sara Mills' model. The object of this study is the construction of language that gives rise to the position of women in news texts. The results of this study are the position of subject-object and writer-reader in the news of information media Tempo.co and Narasi News room